2021
DOI: 10.1080/02699931.2021.1902283
|View full text |Cite
|
Sign up to set email alerts
|

Narrative coherence predicts emotional well-being during the COVID-19 pandemic: a two-year longitudinal study

Abstract: Prior research has shown that narrative coherence is associated with more positive emotional responses in the face of traumatic or stressful experiences. However, most of these studies only examined narrative coherence after the stressor had already occurred. Given the outbreak of the novel coronavirus disease COVID-19 in March 2020 in Belgium and the presence of data obtained two years before (February 2018), we could use our baseline narrative coherence data to predict emotional well-being and perceived soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…This configuration suggests that coherence is a learned skill that involves the construction of more integrated fluent narratives regardless of specific topic or time point. Yet, at the same time, rapid changes in narrative coherence further suggests that narrative is also partly a processing variable, depending on how the individual is processing this particular event in time (see also Vanaken et al, 2021). Our findings thus add to the extant literature by confirming coherence as a pivotal narrative dimension for identity and for well‐being across event valence and over time, and pointing to coherence as emerging from both individual and context factors.…”
Section: Discussionmentioning
confidence: 99%
“…This configuration suggests that coherence is a learned skill that involves the construction of more integrated fluent narratives regardless of specific topic or time point. Yet, at the same time, rapid changes in narrative coherence further suggests that narrative is also partly a processing variable, depending on how the individual is processing this particular event in time (see also Vanaken et al, 2021). Our findings thus add to the extant literature by confirming coherence as a pivotal narrative dimension for identity and for well‐being across event valence and over time, and pointing to coherence as emerging from both individual and context factors.…”
Section: Discussionmentioning
confidence: 99%
“…For now, we conclude that there is a need for training programs focusing on narrative coherence in autistic samples since both negative and positive narratives can show improvements. Especially given that coherent narratives play an important function in our social lives (Vanaken et al, 2021). Regarding other-focused mentalizing abilities, the current training program was able to demonstrate improvements of autistic adults in the Training group regarding accuracy of pictorial (non-verbal) false belief sequencing relative to pretraining, and also showed improved accuracy relative to the control group regarding accuracy of verbal and pictorial true belief sequencing.…”
Section: Summary Of Findingsmentioning
confidence: 72%
“…First, 30% of all the narratives were coded by the two raters after which inter-rater reliability was assessed by calculating Intraclass Correlation (ICC) as in previous research (e.g., Chen et al, 2012 ; Sales et al, 2013 ; Vanaken et al, 2021 ). We also calculated Krippendorff’s alpha, a stricter reliability coefficient.…”
Section: Methodsmentioning
confidence: 99%
“…Namely, it has been shown that chronological incoherence can lead to negative social responses of listeners (Vanaken et al, 2020; Vanaken & Hermans, 2020). Consequently, support from a social network diminishes, which can increase feelings of loneliness or depression in the narrator (Coyne, 1976; Vanaken et al, 2021). The importance of affective subcomponents (emotional elaborations, identity) for our mental health can also be explained, since the ability to emotionally evaluate and interpret our experiences as well as integrate them into our identity has repeatedly been suggested to be critical for our well‐being (Cox & McAdams, 2014; Habermas & Reese, 2015; McAdams & McLean, 2013; Mitchell et al, 2020).…”
Section: Discussionmentioning
confidence: 99%